2005
DOI: 10.1890/04-0922
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biodiversity on Ecosystem Functioning: A Consensus of Current Knowledge

Abstract: Effects of biodiversity on ecosystem functioning: a consensus of current knowledge AbstractHumans are altering the composition of biological communities through a variety of activities that increase rates of species invasions and species extinctions, at all scales, from local to global. These changes in components of the Earth's biodiversity cause concern for ethical and aesthetic reasons, but they also have a strong potential to alter ecosystem properties and the goods and services they provide to humanity. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

168
5,714
42
166

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 6,561 publications
(6,090 citation statements)
references
References 336 publications
(475 reference statements)
168
5,714
42
166
Order By: Relevance
“…When normalized by L/S, degree distributions have a general exponential-type shape [20] indicating that most paths of energy flow through food webs go through relatively few species. This is consistent with species removal experiments in BEF studies, which have suggested a small sub-group of species disproportionately influences productivity [9].…”
Section: Intervalitysupporting
confidence: 90%
See 3 more Smart Citations
“…When normalized by L/S, degree distributions have a general exponential-type shape [20] indicating that most paths of energy flow through food webs go through relatively few species. This is consistent with species removal experiments in BEF studies, which have suggested a small sub-group of species disproportionately influences productivity [9].…”
Section: Intervalitysupporting
confidence: 90%
“…The interplay between intraspecific (e.g., closely related taxa tend to share trophic relationships) and inter-specific (e.g., strong interactions between predators and prey, and plants and pollinators) interactions will have profound effects on food-web structure [63], and the balance of these can determine the occurrence and strength of niche partitioning effects on ecosystem functioning [9]. Most studies have considered food webs as a fixed suite of species with no variation in patterns of connectivity through evolutionary time [64].…”
Section: Linking Individuals To Food Webs To Ecosystem Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is today a consensus that biodiversity losses will result in declining EF if species perform different roles in ecosystems, in other words if they have different functional traits [1][2][3] . Understanding the mechanisms that shape the distribution of species traits within species assemblages has thus become central to the biodiversity-EF research agenda.…”
mentioning
confidence: 99%